Kelas Pesisir untuk Meningkatkan Kemampuan Bahasa Inggris Siswa Sekolah Dasar - Adam, Sutisno; Sailuddin, Sartika Putri (ADMA : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2024)
Community service activities in the form of training to improve English language skills for students at SDN 58 Ternate City. The aim of this service is to provide knowledge and self-development skills for students in Kastela Village, Ternate Island. This ability is expected to improve the foreign language skills of the younger generation and as a form of implementation of the tridharma of higher education to empower society. The target participants for this PKM activity are 30 grade 5 students at SDN 58 Ternate City. The method used in this service is game-based learning with an outdoor class system. The implementation of this community service activity will apply a translanguaging approach as a form of preserving local wisdom by empowering children's mother tongue, namely Ternate, as one of the learning languages. The results obtained from this service are increasing students' knowledge of English using games and instruments. The obstacle faced in this service activity is the students' limited English language skills so that most of the explanation of the activity steps is carried out in Indonesian.